Inflation, Inflationary Tax and Tax Evasion in Algeria: An Empirical Analysis of Underlying Causal Interactions - Feriel Dermechi; Ahmed Zakane (Acta Economica)
This article is an empirical study that aims to deeply examine the effects of the underlying interactions of inflation and inflationary tax on the size of tax evasion in Algeria. Accordingly, the analysis is grounded in the application of the Granger causality test within a vector autoregressive (VAR) model, covering an annual period ranging from 1980 to 2022. The findings reveal that, in the short term, the inflation rate has a positive impact on tax evasion, whereas the inflationary tax exerts a negative influence on it. Our approach strives to interpret these findings through the lens of inflationary financing theory. This theory elucidates how the inflation rate and the implicit revenues it generates contribute to the regulation of the scope of tax evasion in the country.